IMPLEMENTASI KEBIJAKAN PERLUASAN KESEMPATAN KERJA DI KABUPATEN KARAWANG - Dustin Natio Immanuel Sinaga; Tri Yuniningsih (Journal of Management and Public Policy, 2026)
Karawang Regency, as one of the largest industrial areas in Indonesia, still faces the problem of high unemployment, indicating a mismatch between industrial growth and the absorption of local labor. To address this issue, the Karawang Regency Government established a job opportunity expansion policy through Regent Regulation Number 8 of 2016. This study aims to analyze the implementation of the job opportunity expansion policy and to identify the supporting and inhibiting factors in its implementation. This research uses a descriptive method with a qualitative approach, with data collection techniques including interviews, observation, and documentation. The results show that the policy implementation has been carried out through various programs such as job vacancy information services, job training, and increasing local labor absorption; however, it has not been optimal. This is due to several constraints, including limited resources, ineffective policy communication, and insufficient inter-agency coordination. In addition, field practices indicate inconsistencies in policy implementation, such as administrative manipulation of labor data. Therefore, improving the effectiveness of policy implementation is necessary through strengthening coordination, optimizing resources, and enhancing supervision and public outreach so that the policy objectives in reducing unemployment can be achieved more effectively.